Apply the distributive property to the right side of the equation as shown on the board

\(a(b-c)=a\times b-a\times c\)

\(7x+3=6(x-1)+9\)

\(\Rightarrow7x+3=(6)(x)-(6)(1)+9\)

\(\displaystyle\Rightarrow{7}{x}+{3}={6}{x}-{6}+{9}\)

Evaluate the constant terms on the right side as shown on the board

\(7x+3=6x+3\)

Subtract 3 from both sides as shown on the board

\(7x+3-3=6x+3-3\)

Cancelling out +3 and -3 from both sides, we get the equation as shown on the board

\(7x=6x\)

Subtract 6x from both sides as shown on the board

\(7x-6x=6x-6x\)

Cancelling out 6x and -6x from the right side we get the equation as shown on the board

\(7x-6x=0\)

Subtracting 6x from 7x on the left side we get the final value of x as shown on the board

\(x=0\)

Final answer

\(x=0\)